2001
DOI: 10.2486/indhealth.39.106
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Studies of Man-Made Mineral Fibers. Fibrosis-Related Factors.

Abstract: Pneumoconiosis that pursues a chronic course may result from repeated injury and repair caused by dust particles that remain in the lungs, leading to fibrosis. We will introduce in vivo studies concerning these processes using animals exposed to man-made mineral fibers and asbestos. We will report on whether there are developmental changes with the mineral fiber and animal model in proinflammatory cytokine, chemokine, free radicals, proteinase and other genes that lead to injury, as well as in genes that effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Recent studies on humans and rats have shown that CC16 is a sensitive biomarker of respiratory epithelial injury in exposures to welder fumes, glutaraldehyde, nitric oxides, or Al foundry dusts [18][19][20][21][22][23]. Clara cell proteins are involved in the pathogenic mechanisms leading to fibrosis [15,24], chronic obstructive pulmonary disease (COPD) [25,26], and asthma in humans [27][28][29] and in murine asthma model [30,31]. Low level of CC16 was observed in serum and bronchoalveolar lavage fluid (BAL) of active smokers [32].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on humans and rats have shown that CC16 is a sensitive biomarker of respiratory epithelial injury in exposures to welder fumes, glutaraldehyde, nitric oxides, or Al foundry dusts [18][19][20][21][22][23]. Clara cell proteins are involved in the pathogenic mechanisms leading to fibrosis [15,24], chronic obstructive pulmonary disease (COPD) [25,26], and asthma in humans [27][28][29] and in murine asthma model [30,31]. Low level of CC16 was observed in serum and bronchoalveolar lavage fluid (BAL) of active smokers [32].…”
Section: Introductionmentioning
confidence: 99%
“…Fibrogeneity of glass wool fibers as shown in in vitro and in vivo studies [Ishihara, 2001;Morimoto and Tanaka, 2001] and their long biopersistence in the lungs support the possibility that those fibers are the causative agent of this pulmonary process.…”
Section: Discussionmentioning
confidence: 95%
“…The persistence of these fibers in the induced sputum 4 years after biopsy (and more than 9 years after the probable last exposure) indicates a very long bio-persistence [Oberdorster, 2000;Morimoto and Tanaka, 2001;Tanaka et al, 2001].…”
Section: Discussionmentioning
confidence: 99%
“…Increased numbers of bronchoalveolar lavage fluid (BALF) cells after asbestos or other fiberexposure as a result of inflammatory response have been described by numerous authors (Hurbankova & Kaiglova, 1999;Greim et al, 2001;Morimoto & Tanaka, 2001;Osinubi et al, 2000). In our study, a significantly increased number of BALF cells after exposure to amosite in comparison with the control group was observed in the smoker plus 60 mg/m 3 fiber group (by 11.4 %) as well as in the corresponding-dose, non-smoker group (by about 16%).…”
Section: Combined Effect Of Mineral Fibers and Tobacco Smoke On Respimentioning
confidence: 99%